CONTRASTIVE STUDY OF VERBAL ABUSE ON SOCIAL MEDIA: A PRAGMATIC ANALYSIS OF HATE SPEECH IN INDONESIAN AND ENGLISH - Atiqotul Hasanah; Eka Susylowati (Journal of Social, Culture, and Language, 2026)
This research conducts a contrastive study of verbal abuse (specifically hate speech) in Indonesian and English on social media. Using descriptive qualitative method and pragmatic analysis as well as contrastive analysis, this study analyzed ten hate speech comments from Baby Monster's TikTok account (@babymonster_yg_tiktok); five comments in Indonesian and five in English. The data were collected by purposive sampling. Pragmatic analysis focused on the intent, function, and context of the hate speech, while contrastive analysis compared language structure, language use, and verbal abuse strategies in both languages. The results show differences and similarities in the strategies and forms of hate speech in both languages, which are influenced by social and cultural contexts. The analysis found differences in terms of politeness, clarity, and delivery strategies of hate speech. This research contributes to the understanding of the dynamics of hate speech across languages and cultures, and provides insights for the development of effective communication strategies to reduce the spread of hate speech on social media.